System metabolic engineering modification of Saccharomyces cerevisiae to increase SAM production - Liangzhuang Tan; Yuehan Zhang; Ping Liu; Yihang Wu; Zuoyu Huang; Zhongce Hu; Zhiqiang Liu; Yuanshan Wang; Yuguo Zheng (Bioresources and Bioprocessing)
Abstract S-adenosyl-L-methionine (SAM) is an important compound with significant pharmaceutical and nutraceutical applications. Currently, microbial fermentation is dominant in SAM production, which remains challenging due to its complex biosynthetic pathway and insufficient precursor availability. In this study, a multimodule engineering strategy based on CRISPR/Cas9 was established to improve the SAM productivity of Saccharomyces cerevisiae. This strategy consists of (1) improving the growth of S. cerevisiae by overexpressing the hxk2 gene; (2) enhancing the metabolic flux toward SAM synthesis by upregulating the expression of the aat1, met17, and sam2 genes and weakening the synthesis pathway of L-threonine; (3) elevating precursor ATP synthesis by introducing the vgb gene; (4) blocking the SAM degradation pathway by knocking out the sah1 and spe2 genes. The SAM titer of the resulting mutant AU18 reached 1.87 g/L, representing an increase of 227.67% compared to the parental strain. With optimal medium, SAM titer of mutant AU18 reached 2.46 g/L in flask shake fermentation. The SAM titer of mutant AU18 further reached 13.96 g/L after 96 h incubation with a continuous L-Met feeding strategy in a 5 L fermenter. Therefore, with comprehensive optimization of both synthesis and degradation pathways of SAM, a multimodule strategy was established, which significantly elevated the SAM production of S. cerevisiae. This laid a foundation for the construction of hyperproducer for SAM and other valuable amino acids or chemicals.